Advancing the Cognitive Science of Religion through Replication and Open Science. (11th October 2020) - Hoogeveen, Suzanne; van Elk, Michiel
Abstract : The Cognitive Science of Religion (CSR) is a relatively young but prolific field that has offered compelling insights into religious minds and practices. However, many empirical findings within this field are still preliminary and their reliability remains to be determined. In this paper, we first argue that it is crucial to critically evaluate the CSR literature and adopt open science practices and replication research in particular to move the field forward. Second, we highlight the outcomes of previous replications and make suggestions for future replication studies in the CSR, with a particular focus on neuroscience, developmental psychology, and qualitative research. Finally, we provide a "replication script" with advice on how to select, conduct, and organize replication research. Our approach is illustrated with a "glimpse behind the scenes" of the recently launched Cross-Cultural Religious Replication Project, in the hope of inspiring scholars of religion to embrace open science and replication in their own research.